The Effect of Giving Tempeh Nuget and Cork Fish Substance on Weight Gain and Height of School Children in The Sarudik Health Center Area, Central Tapanuli Regency in 2021 - Herlina Tarigan (Institute of Computer Science (IOCS), 2022)
Elementary school age children are an age group that has a fairly high activity both in a state of learning and at rest. Optimal growth and development of primary school-age children depends on the provision of nutrients of good quality and quantity, such as providing intake of tempeh and snakehead fish protein to increase children's growth. Without good nutrition, children will definitely experience nutritional problems, one of which is stunting. Stunting (short) is a nutritional status based on height for age with a z-score of less than-2 elementry school. Categorized as very short if the z-score is less than -3 SD. This study aims to determine the effect of nutrition education and supplementary feeding made from tamban fish on increasing weight and TB in school children in the working area of the Sarudik Health Center, this study was carried out in May–November 2021. This study was a quasi-experimental study with a pre-test research design. and posttest. The research sample amounted to 31 people with male sex 19 people and 12 women.